Innovations in Urban Traffic Management Using Heterogeneous Data Sources and AI: An Integrated Approach - Gómez Pascual, Iván; Ilarri Artigas, Sergio (Jornada de Jóvenes Investigadores del I3A, 2024)
In this brief article, we present our current and future research focused on improving urban traffic management and prediction techniques. Our methodology is based on integrating data from diverse sources and applying advanced analysis and modeling techniques. This approach aims to optimize urban planning and promote more sustainable transportation systems in urban environments, adapting to the changing needs of modern cities.